Infective endocarditis, rheumatoid factor, and anticardiolipin antibodies. Issue 2 (February 1990) - Asherson, R A; Tikly, M; Staub, H; Wilmshurst, P T; Coltart, D J; Khamashta, M; Hughes, G R
Abstract : Serum samples from 22 patients with infective endocarditis were analysed for the presence of antibodies to cardiolipin, false positive Venereal Disease Research Laboratory (VDRL) test, and rheumatoid factor in order to determine the prevalence of anticardiolipin antibodies, their level, and to ascertain whether there was any correlation with the presence of rheumatoid factor. Although the latex test was positive in 10/22 (45%) patients, anticardiolipin antibodies, usually of a low level, were raised in only four (18%), and the VDRL test was positive in two patients in whom other antibodies were negative. These results show a clear discordance between these three tests, indicating that B cell production of these antibodies is separate and distinct. As with other infections which result in anticardiolipin antibody production, no thrombotic events were encountered.